2009
DOI: 10.1038/nrrheum.2009.196
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines and autoimmunity

Abstract: Vaccines have been used for over 200 years and are the most effective way of preventing the morbidity and mortality associated with infections. Like other drugs, vaccines can cause adverse events, but unlike conventional medicines, which are prescribed to people who are ill, vaccines are administered to healthy individuals, thus increasing the concern over adverse reactions. Most side effects attributed to vaccines are mild, acute and transient; however, rare reactions such as hypersensitivity, induction of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
150
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(158 citation statements)
references
References 23 publications
1
150
0
7
Order By: Relevance
“…In fact, the number of active joints was lower after VV in patients with JIA. The question of whether vaccination could induce the onset of symptoms or trigger flares in patients with rheumatic disease is a matter of debate (15,16). There are only 2 published studies regarding the safety of using live vaccines in juvenile rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the number of active joints was lower after VV in patients with JIA. The question of whether vaccination could induce the onset of symptoms or trigger flares in patients with rheumatic disease is a matter of debate (15,16). There are only 2 published studies regarding the safety of using live vaccines in juvenile rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios histopatológicos en estos pacientes han demostrado altos niveles de anticuerpos tipo IgG, células Th1/Th17 y citocinas en la cápsula de silicona de los implantes protésicos mamarios 38,39 . Adicionalmente, la silicona se puede filtrar desde las prótesis hacia tejidos adyacentes o diseminarse distalmente, induciendo una reacción a cuerpo extraño caracterizada por activación de células inmunitariass, fibrosis y la formación de granulomas que contienen silicona [40][41][42][43][44][45][46] . La teoría de una respuesta autoinmune/inflamatoria con la formación de autoanticuerpos, células reactivas y citocinas, ha sido apoyada por modelos animales [47][48][49] .…”
Section: Asiaunclassified
“…Over many years of vaccination case reports surfaced of conditions such as arthritis, Guillain-Barré syndrome, meningitis, chronic fatigue syndrome and vasculitis, being associated with a history of vaccination [7]. Arthritis after vaccination with DTP (diphtheria-tetanus-pertussis), transverse myelitis after oral polio vaccination and autoimmune thrombocytopenia after vaccination with MMR (measles-mumpsrubella) vaccine [8] have been reported, while the Haemophilus influenzae B vaccine (HiB) has been linked with the occurrence of insulin-dependent diabetes. The article by Classen et al demonstrated that in NOD mice (diabetes-prone non-obese diabetic mice) after immunization with HiB vaccine, an increased risk of developing diabetes occurred.…”
Section: S T R E S Z C Z E N I Ementioning
confidence: 99%
“…Od wielu lat pojawiają się opisy przypadków wystąpienia takich schorzeń, jak zapalenie stawów, zespół Guillaina-Barrégo, zapalenie opon mózgowo-rdzeniowych, zespół przewlekłego zmęczenia i zapalenie naczyń, które można powiązać z przebytym szczepieniem [7]. Zapalenie stawów opisywano po szczepieniu DTP (krztusiec-tężec-błonica), poprzeczne zapalenie rdzenia po zastosowaniu szczepionki doustnej polio, autoimmunologiczną trombocytopenię obserwowano zaś po szczepieniu MMR (świnka-ospa-różyczka) [8]. Szczepienie przeciw Haemophilus influenzae B (HiB) jest wiązane z wystąpieniem insulinozależnej cukrzycy.…”
Section: S T R E S Z C Z E N I Eunclassified